Abelha Plebeia cf. flavocincta como potencial polinizador do cacaueiro (Theobroma cacao L.) no semiárido brasileiro - Lemos, Camila Queiroz (2014)
The culture of cocoa has been taken to drier areas to prevent fungal diseases such as “vassoura de bruxa” (Moniliophtora perniciosa), however it is not known how culture would behave in these new conditions, including the existence of natural pollinators. Therefore this study aims to study the floral biology, flower visitors and potential pollinators of cacao and the use of bee Plebeia cf. flavocincta in cocoa cultivation in the Brazilian semiarid region. The study was conducted from October to December of 2013 in the farm Frutacor, in the municipality of Russas - CE. This study has selected the variety of cacao CA1. The results obtained in relation to floral biology showed that the opening of the flowers of the cacao occurred gradually starting at 15h until 5 am the next day. Pollinated flowers presented fruit formation seven days after opening and the others not pollinated abscised 36h after anthesis. The range selected for study had an average of 859 ± 25 206.86 inflorescences per plant and a total of 5654.58 individuals (buds and flowers), with 87.99 % of flower buds (4975.93 ± 1197.92) and 12.01% of flowers (678.55 ± 34.09). Flowers found, 85 % were new and 15 % old. Fruit yield per plant was estimated by the total number of fruits count in five plants with a mean of 72.60 ± 34.09 per plant. About the application for pollination, it was found that only in the free one occurred fruit formation. In assessing the insect community present in the area of culture using pan traps were collected 292 individuals in four order: Diptera the most abundant with 179 individuals (61,30%), followed by Hymenoptera (27,05%), Coleoptera (7,19%), Lepdoptera (2,39%) and others (2,39%). As regards the use of bees Plebeia in cocoa growing, it was observed that the activity of flight occurred more frequently in the morning and early afternoon, focusing peak input and output in colonies of bees from 11:00 am to 13:00 pm. The nectar/water was the main resource gathered almost the whole of the observations. Although bees have not been observed in cocoa flowers, pollen culture found in food pots and in the body of foragers, pollen basket and head, indicated that they effectively visited the culture.